Framing Religious Hoaxes: Logical, Religious, and Legal Perspectives in Indonesia - Fathurrohman, Rizal; Anna, Dian Nur; Sibawaihi, Sibawaihi; Fahmi, Muhammad Zaki (Religious: Jurnal Studi Agama-Agama dan Lintas Budaya, 2024)
This study aims to analyze religious hoaxes on social media in Indonesia by examining their logical, religious, and legal dimensions. It highlights how these hoaxes, often framed through logical fallacies and spread via digital platforms, exacerbate social polarization and interfaith tensions. The study used a descriptive qualitative approach, focusing on high-profile cases involving religious hoaxes during 2020–2021. The researchers collected data from social media posts, comments, and videos on platforms such as YouTube and Twitter, as well as from secondary sources, including news articles, legal documents, and religious texts. The findings reveal the strategic use of logical fallacies such as ad hominem and argumentum ad populum, the exploitation of sensitive religious issues, and the amplification of divisive narratives through digital platforms. These hoaxes significantly impact societal harmony, resulting in polarization, theological confusion, and heightened interfaith tensions. The study underscores the critical need to enhance media literacy, foster interfaith dialogue, and enforce digital content regulations. These strategies can mitigate the impact of religious hoaxes and promote a more informed, cohesive society. This research integrates logical, religious, and legal frameworks to analyze religious hoaxes comprehensively. Addressing the intersection of these perspectives offers a unique contribution to understanding and mitigating the societal impacts of digital misinformation.